Impact of Ebola Education on Knowledge Level of Ebola Disease among Primary School Teachers in Benin Metropolis - Agwubike , Elias O. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The paper determined the efficacy of a two-day Ebola Education on knowledge and awareness level of primary school teachers in Benin Metropolis of Nigeria. Two research questions were raised and two corresponding hypotheses were formulated which were tested at 0.05 level of significance. A total of 587 teachers proportionately selected from the primary schools in three Local government areas that make up Benin metropolis were used. That served as 20% of the population of2,933 primary school teachers in the area. The education modality centered on six key areas of Ebola. The participants were pre and post tested prior to and after the Ebola Education intervention. Frequency counts, percentages and chi-square were the statistics used for data analysis. The results revealed the teachers’ significant differential knowledge of Ebola prior to Ebola Education. There was also significant improvement on Ebola knowledge after the education intervention. It was recommended that a well- planned Ebola Education be organized for primary school teachers (and pupils) outside Benin metropolis. Moreover, a similar Ebola Education be extended to teachers of secondary and tertiary educational institutions in Nigeria. There is the need to institute a proactive policy regarding Ebola prevention to guide against complacency that is likely to encourage Ebola re-emergence in Nigeria